AMIR TEMUR AND THE ARCHITECTURE OF THE TIMURID PERIOD AS WELL AS THE HISTORY OF THE CITY OF SAMARKAND ARE EXAMINED IN WESTERN EUROPEAN HISTORIOGRAPHY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article is about the unique position of Central Asia in world civilization, its achievements in the fields of science, culture, architecture, especially its high development during the period of Amir Temur and the Timurids, the culture and architecture of Central Asia, especially in Samarkand It shows how the work of European, especially Italian, English, French and German historians is treated in the work. At the same time, the situation of Amir Temur's capital Samarkand in the 19th century is covered.